(untitled) (Indian Journal of Animal Production and Management, 2024)
This study investigated the impact of high milk feeding on the body weight of 25 early-weaned crossbred (HF×K) calves at Livestock Research Station, Kamdhenu University, Anand, Gujarat, over 182 days. Calves were divided into five treatment groups with equal numbers of male and female calves. Colostrum was provided for the first 3 days, followed by 4 liters of fresh milk daily for the first two weeks. The total milk quantity offered in T1, T2, T3, T4 and T5 was 252, 329, 353.5, 378, 402.5 kg respectively, to study the faecal consistency and behavior of calves. The faecal consistency and behaviour of calves after one hour during morning milk feeding was observed among the experimental calves for milk feeding of 63 days. The observation shown that calves of T5 group (higher quantity of milk feeding) defecate less normal faeces with incidences of water faeces. The calves of T5 group exhibited discomfort sign like; standing up/down, licking and kicking of abdomen after ingesting milk. The high quantity of milk feeding at a stretch (T5) caused behavior abnormality and loose faeces in calves. The feeding of high amount of (T5) is not advisable for the welfare and intestinal health of crossbred calves.